THE EFFECT OF MARKET ORIENTATION AND INNOVATION ABILITY ON ENTERPRISE PERFORMANCE: A PRACTICE OF STRUCTURAL EQUATION MODELLING ANALYSIS: A RESEARCH ON SMES - Guleş, Hasan Kürşat; Zerenler, Muammer; Çağlıyan, Vural; Şener, Tuğba; Karaboğa, Kazım (European Scientific Journal, ESJ, 2015)
Enterprises can be successful in global competition by creating the useful information, which provides competitive superiority, and spreading this information to the whole enterprise, implementing it in a short time, developing new products, processes, markets and organizations. It is expected to make an effect which increases the performance of the enterprise by successfully implementing this information in the innovation process. For this, enterprises should listen their customers and make their products according to their demands and offer them to the market. Strategic orientations of the enterprises have an important effect on their performances. In order to meet the expectations of customers, the ideas to improve new product is dependent on developing a systematic novelty culture which is technology and innovation-oriented. Customer and marketoriented practices have important effects on enterprises’ intellectual elements and profitability. In this work, the effect of market orientation and innovativeness ability on the performance of the enterprise is studied. Market orientation is studied under three sub-dimensions: Competitor-oriented, customer-oriented and coordination among the functions. Market orientation, innovativeness ability and performance of the enterprise is analyzed with constitutional equality modelling. As a result, secret variables like competitor-oriented and coordination among the functions haven’t a meaningful effect on enterprise performance, however innovativeness ability and competitor orientation variables have a positive meaningful effect on enterprise performance. Innovativeness ability has more direct effect on enterprise performance than market orientation dimensions.